Development of a novel outcome prediction score (PEDSS) for pediatric convulsive status epilepticus: A longitudinal observational study. (13th November 2020) - Tiwari, Richa; Chakrabarty, Biswaroop; Gulati, Sheffali; Jauhari, Prashant; Lodha, Rakesh; Sankar, Jhuma; Kumar, Atin; Pandey, Ravindra Mohan; Upadhyay, Ashish; Gupta, Juhi; Sinha, Rahul
Abstract: Objective: The objectives of this study were to evaluate ENDIT score and develop a novel outcome prediction score for outcome of pediatric convulsive status epilepticus (CSE) at the hospital and 3 months postdischarge. Methods: Children and adolescents aged 1 month to 14 years, presenting with CSE to a tertiary care teaching center in North India from January 2017 to March 2019, were screened for enrollment. In‐hospital and 3‐month postdischarge outcome were defined as poor if Pediatric Cerebral Performance Category Scale (PCPCS) score dropped by ≥2 levels. Results: Overall, 61 patients were enrolled for final analysis after applying exclusion and inclusion criteria. The area under the receiver operating characteristic (ROC) curve for ENDIT score in predicting mortality and differentiating good from poor outcome at the hospital and at 3 months postdischarge was 0.74 (95% confidence interval [CI] = 0.58‐0.89), 0.7 (95% CI = 0.57‐0.83), and 0.72 (95% CI = 0.6‐0.82), respectively. Based on predictors in the present cohort that were significantly different between good and poor outcome cases at the hospital and 3 months postdischarge, a new six‐point score named PEDSS (pre–status epilepticus PCPCS, background electroencephalographic abnormalities, drug refractoriness, semiology, and critical sickness) was developed. The area under ROC curves for PEDSS score in predicting mortality and differentiating good from poor outcome at the hospital and at 3 months postdischarge were 0.93 (95% CI = 0.87‐0.99), 0.8 (95% CI = 0.7‐0.9), and 0.89 (95% CI = 0.8‐0.96), respectively. The best cutoff PEDSS scores for predicting mortality and poor outcome at the hospital and at 3 months postdischarge were ≥4, ≥3, and ≥3, respectively. Significance: The PEDSS score has high predictive accuracy for mortality and differentiating good from poor outcome at the hospital and 3 months postdischarge in pediatric CSE. Future studies should be planned to validate it in various geographical and health care settings and in adults.